Dinamika Konflik Interpersonal dan Ketegangan Kerja: Analisis Fenomena Permasalahan Antar-Karyawan pada PT. ROKOK ELEKTRIK ENAK - Irene Avianti Putri; Pearltama Rayhan P.U; Intan Wijaya Liroga; Muhammad Auf Vulvian Firjatulloh; Tan Evan Tandiyono (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The modern manufacturing and retail industry, particularly in the e-cigarette sector, demands high productivity, which often triggers friction between individuals within organizations. PT. Rokok Elektrik Enak faces internal challenges in the form of inter-employee conflicts that impact job stability. This qualitative research aims to understand and explain this social phenomenon through in-depth analysis. The research method used is inductive, with data collected through observation and interviews to capture the nuances and individual variations in conflict. The results indicate that the root of the problem stems from ineffective communication, differences in values between generations (senior vs. junior), and high ego. Psychological impacts found include decreased motivation,